Analysis of CCS Technology Applied in Green Building - Pan, Shijin (Transactions on Engineering and Technology Research, 2024)
As the global climate change crisis intensifies, the integration of green building practices with carbon capture and storage (CCS) technology is increasingly emerging as a focal point of research within the architectural domain. Green buildings prioritize resource efficiency, environmental sustainability, and long-term viability, while CCS technology serves as an effective mechanism for mitigating carbon emissions. This paper examined the application of CCS technology in green buildings and identifies its significant potential across various stages of building design, construction, and operation. Firstly, CCS technology can substantially reduce carbon emissions during the production processes of construction materials—particularly in high-emission sectors such as cement and steel manufacturing. Furthermore, by synergizing CCS technology with energy systems utilized in building operations, it becomes feasible to capture carbon emissions generated from routine energy consumption, thereby facilitating a near-zero carbon footprint. Nonetheless, challenges related to integration complexity and elevated costs hinder the deployment of CCS technology within existing structures—especially older buildings where spatial constraints and infrastructural limitations pose considerable obstacles. The lack of clear economic incentives has deterred numerous construction projects from investing in CCS solutions, further constraining its broader adoption within the built environment.